RP-HPLC Method Development and Validation for the Estimation of Methylcobalamin in Bulk - BS Muddukrishna (Journal of Global Pharma Technology, 2017)
The subsequent artefact entail of extremely subtle and informal Reversed phase HPLC (RP-HPLC) technique for approximation ofMethylcobalamin in large quantity. Shimadzu LC-20-AD(Kyoto, Japan), with auto sampler and (PDA/UV) detector was used for the separation of Methylcobalamin.C18 Hypersil BDS (5.0 micron,150 x 4.6mm) column was aimed at the separation and mobile phase(MP) comprising of(55:45 v/v) Methanol:o-phosphoric acid 0.02%v/v pH 2.3 was cast-offby keeping the rate offlow1 ml/minalong the effluents supervised on 223nm. linearity is undeviating having line equationf(x) =4.87512e-006*x-0.702284 with correlation coefficient(R2) of 0.997. Theprocessremained precise with 0.5% RSD(intra-day precision)&(Inter-day precision) is 0.43%. The LOD & LOQ was0.1499μg/ml and 0.4542μg/ml respectively.The establishedprocess wasvalidated forlinearity,system suitability,precision, and robustness; henceforthverifies in order that this one is exceedinglyrelevantto approximate Methylcobalamin in routine analysis.Methods name: Estimation of Methylcobalaminby HPLC.Keywords: Methylcobalamin, Reverse phase hplc (RP-HPLC), Validation and chromatography.